2014
DOI: 10.4103/1319-3767.132993
|View full text |Cite
|
Sign up to set email alerts
|

Clinical epidemiology and phenotypic characteristics of Crohn′s disease in the central region of Saudi Arabia

Abstract: Background/Aims:Despite the remarkable increase in the incidence of Crohn's disease among Saudis in recent years, data about Crohn's disease in Saudi Arabia are scarce. The aim of this study was to determine the clinical epidemiology and phenotypic characteristics of Crohn's disease in the central region of Saudi Arabia.Patients and Methods:A data registry, Inflammatory Bowel Disease Information System (IBDIS), was used to register Crohn's disease patients who presented to the gastroenterology clinics in four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 49 publications
5
13
1
Order By: Relevance
“…Studies conducted in Saudi Arabia have found that the most common EIMs found in UC patients are osteopenia, followed by EN, and then arthritis, with a prevalence of 30.5%, 23.8%, and 17.5%, respectively [ 19 ]. However, only 5% of CD patients have dermatological manifestations, 15.5% have arthritis or arthralgia, and 2.3% have deep vein thrombosis (DVT) [ 20 ]. A study in Riyadh showed that 32% of pediatric IBD patients have EIMs, most of them have indeterminate colitis [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in Saudi Arabia have found that the most common EIMs found in UC patients are osteopenia, followed by EN, and then arthritis, with a prevalence of 30.5%, 23.8%, and 17.5%, respectively [ 19 ]. However, only 5% of CD patients have dermatological manifestations, 15.5% have arthritis or arthralgia, and 2.3% have deep vein thrombosis (DVT) [ 20 ]. A study in Riyadh showed that 32% of pediatric IBD patients have EIMs, most of them have indeterminate colitis [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study that explored the epidemiologic, clinical, and phenotypic charactersitics of UC patients in four tertiary care hospital in three cities in Saudi Arabia, no significant difference in the percentages of male and female patients affected by UC was noted and the majority of UC patients were young (e.g., 17–40 years of age) [14]. Likewise, the majority of CD patients were young (e.g., 17–40 years of age) according to a multi-center study that explored the characteristics of CD patients in Saudi Arabia, however, the majority of patients were male [15].…”
Section: Introductionmentioning
confidence: 99%
“…[3] As such, IBD is no longer considered a rare disorder in several parts of the world, including areas where the disease prevalence was previously considered to be low, such as in Middle Eastern countries. [45] A study conducted in Bahrain in 2017 by Abdulla et al . estimated the incidence and prevalence of CD and UC among patients attending a particular primary healthcare (PHC) center.…”
Section: Introductionmentioning
confidence: 99%